Descripción anatómica e histológica de las gónadas en Sabaleta (Brycon henni, Eigenmann 1913) (2006)
ABSTRACT: Brycon henni is a colombian endemic characid. The purpose of this research was to describe in anatomical and histological level the gonads of this fish. Monthly for one year, Brycon henni specimen were caught, fishes were sacrificed, then a dissection was performed; the gondosomatic and hepatosomatic index were calculated, the gonads were fixed in formol 10% and processed with routine histological techniques, 7ìm thickness cuts were made, the cuts were coloreated with hematoxilin-eosin. Ovaries of B. henni are paired, lengthened, and symmetrical organs, they are located ventrally to the swimming bladder of the female. In the first stadiums of development, the ovary present a pink color, as it advances in maturity, it appears of orange color, given for oocites observed. Depending on size, form, coloration and visualization of oocites, we qualified ovaries in stadium I, II or III. Testicles of B. henni are paired and lengthened organs, they present white color, and they are located ventrally to the swimming bladder of the male. The immature testicles are symmetrical organs, as testicles advance in the development, asymmetry is observed between them. Histologically we described oogonium and the phases of the follicular complex: chromatin nucleolus, perinucleolar, cortical alveolus and vitellogenesis. For the testicle, we described the organization of the lobes and the cells of the spermatic line: spermatogonium, spermatocytes, spermatides and spermatozoa. The gonadal development in B. henni showed inverse relation with rainfall.